High-altitude pulmonary hypertension is associated with a free radical-mediated reduction in pulmonary nitric oxide bioavailability - Bailey, Damian M.; Dehnert, Christoph; Luks, Andrew M.; Menold, Elmar; Castell, Christian; Schendler, Guido; Faoro, Vitalie; Gutowski, Mariusz; Evans, Kevin A.; Taudorf, Sarah; James, Philip E.; McEneny, J.; et al. (The journal of physiology, 2010)
High altitude (HA)-induced pulmonary hypertension may be due to a free radical-mediated reduction in pulmonary nitric oxide (NO) bioavailability. We hypothesised that the increase in pulmonary artery systolic pressure (PASP) at HA would be associated with a net transpulmonary output of free radicals and corresponding loss of bioactive NO metabolites. Twenty-six mountaineers provided central venous and radial arterial samples at low altitude (LA) and following active ascent to 4559 m (HA). PASP was determined by Doppler echocardiography, pulmonary blood flow by inert gas re-breathing, and vasoactive exchange via the Fick principle. Acute mountain sickness (AMS) and high-altitude pulmonary oedema (HAPE) were diagnosed using clinical questionnaires and chest radiography. Electron paramagnetic resonance spectroscopy, ozone-based chemiluminescence and ELISA were employed for plasma detection of the ascorbate free radical (A·−), NO metabolites and 3-nitrotyrosine (3-NT). Fourteen subjects were diagnosed with AMS and three of four HAPE-susceptible subjects developed HAPE. Ascent decreased the arterio-central venous concentration difference (a-cvD) resulting in a net transpulmonary loss of ascorbate, α-tocopherol and bioactive NO metabolites (P < 0.05 vs. LA). This was accompanied by an increased a-cvD and net output of A·− and lipid hydroperoxides (P < 0.05 vs. sea level, SL) that correlated against the rise in PASP (r= 0.56-0.62, P < 0.05) and arterial 3-NT (r= 0.48-0.63, P < 0.05) that was more pronounced in HAPE. These findings suggest that increased PASP and vascular resistance observed at HA are associated with a free radical-mediated reduction in pulmonary NO bioavailability.